2016
DOI: 10.1111/sed.12257
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and size gradation of saturated gravel with percolated fines

Abstract: This is the accepted version of the following article: [Núñez-González, F., Martín-Vide, J. P., Kleinhans, M. G. (2016), Porosity and size gradation of saturated gravel with percolated fines. Sedimentology, 63: 1209–1232. doi: 10.1111/sed.12257], which has been published in final form at http://onlinelibrary.wiley.com/doi/10.1111/sed.12257/abstractFine particles may infiltrate through coarse alluvial beds and eventually saturate the subsurface pore space. It is essential to understand the conditions that lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…If finer sediments are supplied at a small rate to a riverbed covered by a completely developed armor coat, the fine sediments can infiltrate into the interstitial spaces of the coarser bed material and move into void spaces. As a result of fine sediment exchange in void space, the ratio of void space over the total amount of gravel-bed and the porosity change [1,2]. The study of porosity variation plays an important role for fluvial geomorphology assessment and in river ecosystem management.…”
Section: Introductionmentioning
confidence: 99%
“…If finer sediments are supplied at a small rate to a riverbed covered by a completely developed armor coat, the fine sediments can infiltrate into the interstitial spaces of the coarser bed material and move into void spaces. As a result of fine sediment exchange in void space, the ratio of void space over the total amount of gravel-bed and the porosity change [1,2]. The study of porosity variation plays an important role for fluvial geomorphology assessment and in river ecosystem management.…”
Section: Introductionmentioning
confidence: 99%
“…Núñez‐González et al . [] generalized Cui's equations to consider fine material with an extended grain size distribution. The derived equations for nonuniform fine sediment infiltration are summarized as follows.…”
Section: General Equations For Infiltration Of Sediment Mixturesmentioning
confidence: 99%
“…Time increments and q T were selected to assure the fulfillment of q T Δt / Δz < 0.001; for this condition, when performing simulations with a simplified version of the new model, Núñez‐González et al . [] showed that the influence of time and depth increments in the final infiltrated fines content is almost negligible.…”
Section: Model Calibrationmentioning
confidence: 99%
See 2 more Smart Citations